2016
DOI: 10.1021/acs.jpcc.6b04229
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Brønsted and Lewis Acid Sites in Acetalization of Glycerol over Modified Mesoporous Cellular Foams

Abstract: The main objective of this work is to determine which kind of acidic sites, Brønsted (BAS) or Lewis (LAS), are more active and stable in the glycerol acetalization to solketal by means of Raman-monitoring. For this purpose, the mesoporous cellular foams (MCFs) were modified to obtain materials containing exclusively BAS occurring in different number and strength (samples MP-MCF (MP = (3mercaptopropyl)trimethoxysilane) and CS-MCF (CS = 2-(4chlorosulfonylphenyl)ethyltrimethoxysilane)) or the material containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(35 citation statements)
references
References 65 publications
3
28
0
4
Order By: Relevance
“…The Raman bands of glycerol were rather weak in this spectral window, being located near 680 cm −1 . The most informative bands were those at 638 and 648 cm −1 , corresponding both to solketal, and that near 730 cm −1 associated to the formation of a glycerol and acetone adduct formed before cyclization into solketal, as pointed out recently by Stawicka and co‐workers . The formation of the intermediate was apparent from the first few minutes and its evolution depended strongly on the catalytic system.…”
Section: Resultsmentioning
confidence: 55%
“…The Raman bands of glycerol were rather weak in this spectral window, being located near 680 cm −1 . The most informative bands were those at 638 and 648 cm −1 , corresponding both to solketal, and that near 730 cm −1 associated to the formation of a glycerol and acetone adduct formed before cyclization into solketal, as pointed out recently by Stawicka and co‐workers . The formation of the intermediate was apparent from the first few minutes and its evolution depended strongly on the catalytic system.…”
Section: Resultsmentioning
confidence: 55%
“…The data in Table 1 confirmed that strength of BAS is comparable for all the samples. The value of A 200 /A 150 nearly close to unity is characteristic of strong acid sites [30,31]. The relationship between the pressure drop and the flow rate is of practical significance, providing additional knowledge which is useful in assessing process economics.…”
Section: Introductionmentioning
confidence: 99%
“…The data in Table 1 confirmed that strength of BAS is comparable for all the samples. The value of A200/A150 nearly close to unity is characteristic of strong acid sites [30,31]. The identification of acid sites and their strength were studied using pyridine (Py) adsorption combined with Fourier transform infrared (FTIR) studies.…”
Section: Introductionmentioning
confidence: 99%
“…1PDSABEA sample showed 100% selectivity, but modification of the BEA catalysts to be trickier, due to controlled dealumination. Different metal loaded catalysts showed decrease in their activity after 3–4 recycles with relatively poor selectivity due to leaching. BEA sample, also showed deactivation for the acetone due to high reactivity after several usage cycles.…”
Section: Resultsmentioning
confidence: 99%